Harnessing adjuvant-induced epigenetic modulation for enhanced immunity in vaccines and cancer therapy - Megdiche, Yasmine; Salerno-Gonçalves, Rosângela (Frontiers in Immunology, 2025)
Adjuvants are crucial in vaccines and cancer therapies, enhancing therapeutic efficacy through diverse mechanisms. In vaccines, adjuvants are traditionally valued for amplifying immune responses, ensuring robust and long-lasting protection against pathogens. In cancer treatments, adjuvants can boost the effectiveness of chemotherapy or immunotherapy by targeting tumor antigens, rendering cancer cells more vulnerable to treatment. Recent research has uncovered new molecular-level effects of the adjuvants, mainly through epigenetic mechanisms. Epigenetics encompasses heritable modifications in gene expression that do not alter the DNA sequence, impacting processes such as DNA methylation, histone modification, and non-coding RNA expression. These epigenetic changes play a pivotal role in regulating gene activity, influencing immune pathways, and modulating the strength and duration of immune responses. Whether in vaccines or cancer treatments, understanding how adjuvants interact with epigenetic regulators offers significant potential for developing more precise, cell-targeted therapies across various medical fields. This review delves into the evolving role of adjuvants and their interactions with epigenetic mechanisms. It also examines the potential of harnessing epigenetic changes to enhance adjuvant efficacy and explores the novel use of epigenetic inhibitors as adjuvants in therapeutic settings.